Information infrastructure of contemporary humanities and the digital humanities development as a cause of creating new information barriers. A Polish case. - Osiński, Zbigniew (Digital Scholarship in the Humanities, 2019)
Purpose—To identify new information barriers created in the process related to the formation and transfer of humanistic scientific knowledge. Methodology—The reanalysis of the data collected during the earlier research projects. Results—Information barriers were identified, which are created by incomplete bibliographic databases, some solutions used in publishing on the Internet, the low level of information competencies of many humanists, their adverse attitude to open access, and by the education system that prefers knowledge transmission in the linear and text form. Conclusion—New information barriers effectively reduce research capabilities of many humanists, thereby creating a communication barrier between traditional and digital humanists.